Comparison of PSA-density of the transition zone and whole gland for risk stratification of men with suspected prostate cancer: A retrospective MRI-cohort study. Issue 120 (November 2019) - Schneider, Aurelia F.; Stocker, Daniel; Hötker, Andreas M.; Eberli, Daniel; Rupp, Niels J.; Donati, Olivio F.; Becker, Anton S.
Highlights: The prostate-specific antigen density (PSAD) was calculated for the TZ (TZPSAD). TZPSAD may be a better surrogate marker for cancer aggressiveness than PSAD. A TZPSAD threshold of 0.22 ng/ml 2 may help in risk stratification. Abstract: Purpose: To compare the correlation of transition zone prostate-specific antigen density (TZPSAD) versus whole gland (WG) density (PSAD) with Gleason score. Methods: In this single-center, retrospective cohort study, men undergoing MRI of the prostate in 2015 and 2016 who had a transperineal template saturation biopsy within 6 months of MRI were included (n = 178; median age 64 y, interquartile range [IQR] 58–68 y; PSA 6.6 ng/ml, 4.6–9.7 ng/ml). The WG and TZ were segmented voxel-wise on T2-weighted transverse planes. The volumes and corresponding PSA-densities were calculated. Correlations with the Gleason score were assessed with Spearman's rho. Optimal thresholds of the PSA densities were computed using the Youden Index of the receiver-operating-characteristics curve. A p-value of ≤ 0.05 was considered statistically significant. Results: Median WG volume was 45 ml (IQR: 33.9–58.7 ml, range: 17.2–165.3 ml), median volume of the TZ was 27.3 ml (IQR: 19.2–39.3 ml, range: 9.0–141.1 ml). Both PSA density values, PSAD and TZPSAD, correlated significantly with the Gleason score: The PSAD (rho = 0.39) showed significantly weaker correlation than the TZPSAD (rho = 0.44, p = 0.05). ROC analysis revealed an ideal cut-off of 0.15 ng/ml 2 for PSAD (95%-CI: 0.09–0.16 ng/ml 2 ) and 0.22 ng/ml 2 for the TZPSAD (0.15-0.32 ng/ml 2 ) for discrimination between Gleason 3 + 4 and 4 + 3. Conclusion: The TZPSAD exhibited a stronger correlation with cancer dedifferentiation than PSAD and may thus be a better surrogate marker for cancer aggressiveness than PSAD. Moreover, the TZPSAD threshold of 0.22 ng/ml 2 may help in risk stratification of men with suspected PCa.